Disorganized and unresolved states in adulthood. (February 2019) - Jacobvitz, Deborah; Reisz, Samantha
Highlights: Fear related to traumatic memories can result in disorganized adult mental states. Mothers who are unresolved may display frightening behavior toward their infants. Disorganization can predispose individuals to dissociative mental processes/states. Adult disorganization can also be conceptualized as fear of the romantic partner. Stability studies suggest unresolved loss may be more readily repaired than abuse. Abstract : Fear plays a central role in attachment theory and disorganization in adulthood. Fear associated with traumatic memories interferes with resolution of trauma resulting in disorganized mental states, captured as unresolved/disorganized speech surrounding loss and/or abuse in the Adult Attachment Interview. Mothers who are unresolved experience fear stemming from traumatic memories and display frightening behavior towards their infants. Disorganization can predispose individuals to dissociative mental processes, including altered states (absorption), PTSD, and depersonalization. Social psychologists have conceptualized adult disorganization as fear of the romantic partner. Studies examining stability of adult disorganization indicate unresolved loss is more readily resolved than unresolved abuse. Understanding disorganization in adulthood, including experiences that support reparation and reorganization, is important for developing effective interventions.